2016
DOI: 10.18273/revion.v29n1-2016005
|View full text |Cite
|
Sign up to set email alerts
|

Evaluación de la co-digestión anaerobia de lodos de aguas residuales municipales con residuos de alimentos

Abstract: ResumenLa digestión anaerobia es un proceso ampliamente utilizado para el tratamiento de los lodos producidos en las plantas de tratamiento de agua residual, debido a sus ventajas técnicas y económicas. Este artículo presenta un estudio en el que se evaluó la co-digestión de lodos de aguas residuales con residuos de alimentos (RA) como una estrategia para optimizar la digestión de los lodos. Se realizaron mono-digestiones y co-digestiones de los sustratos en condiciones mesofílicas (35°C) usando reactores por … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
1
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 10 publications
(4 citation statements)
references
References 20 publications
0
1
0
Order By: Relevance
“…In addition, BMP assays are commonly expressed in different units, which makes comparison between studies difficult when making a bibliographic review, as shown in Table 2. There are factors that could affect the BMP values obtained between this trial and those reported in the literature [64]; for example, in our study, the agitation was constant, and in a similar study conducted by Julio [28], the agitation was manual. This condition can affect mass transfer between substrates and microorganisms [65].…”
Section: Digestivity Assays and Biochemical Methane Potentialmentioning
confidence: 53%
See 1 more Smart Citation
“…In addition, BMP assays are commonly expressed in different units, which makes comparison between studies difficult when making a bibliographic review, as shown in Table 2. There are factors that could affect the BMP values obtained between this trial and those reported in the literature [64]; for example, in our study, the agitation was constant, and in a similar study conducted by Julio [28], the agitation was manual. This condition can affect mass transfer between substrates and microorganisms [65].…”
Section: Digestivity Assays and Biochemical Methane Potentialmentioning
confidence: 53%
“…The anaerobic biomass present in the digested sludge makes it suitable for use as inoculum [25]. There are several studies where it has been used as an inoculum in the co-digestion of substrates such as grease traps [26], wood chips [27], and organic waste [28].…”
Section: Introductionmentioning
confidence: 99%
“…Respecto a los lodos de las plantas de tratamiento de aguas residuales (PTAR), en el proceso de compostaje se hicieron mono digestiones y codigestiones anaerobias; es decir, diversas mezclas de lodos de aguas residuales con residuos alimenticios para generar biogás en reactores por lotes en condiciones mesofílicas, dando como resultado que la codigestión genera la más alta producción de metano, dado que los residuos de alimentos proveen carbono orgánico a los lodos, optimizando la producción de biogás y por ende mejorando la relación C/N (Julio, Peláez & Molina, 2016). Además, trabajaron con un reactor para producir biogás a partir de lodo fresco del tratamiento de aguas residuales en condiciones mesofílicas, el digestor fue operado a diferentes cargas de alimentación durante 20 días, de este estudio es evidente que si el digestor es operado con mayores cargas de biomasa, menor será el tiempo de retención hidráulica (TRH) y el sistema se volverá más estable.…”
Section: Sosa Et Al (2016)unclassified
“…Currently, it is common to incorporate waste sludge in agricultural soils, as it reduces the addition of commercial fertilizers, improves their fertility, increases water retention capacity and reduces soil erosion [25]. Sludge acts as a soil conditioner to facilitate the transfer or provide nutrients, increase water retention and improve soil fitness for cultivation [26]. Sludge also serves as a partial substitute for expensive chemical fertilizers [4].…”
Section: Introductionmentioning
confidence: 99%